Nuevos antecedentes en el comportamiento del virus de la diarrea viral bovina. Situación en Chile - Celedón V., María O. (Avances en Ciencias Veterinarias, 1993)
In this general article are presented recent findings about molecular aspects that explain the dynamic of biologic, antigenic and pathogenic behavior of bovine viral diarrhea virus and a new syndrome associated with this virus. Beside, it is discussed the situation of the bovine viral diarrhea/mucosal disease in Chile. Key words: Virus, bovine viral diarrhea, bovine. Palabras claves: Virus, diarrea viral bovina, bovinos.